Public acceptance and uptake of oesophageal adenocarcinoma screening strategies: A mixed-methods systematic review - Jasmijn Sijben; Yonne Peters; Kim van der Velden; Linda Rainey; Peter D. Siersema; Mireille J.M. Broeders (EClinicalMedicine, 2022)
Summary: Oesophageal adenocarcinoma (OAC) is increasingly diagnosed and often fatal, thus representing a growing global health concern. Screening for its precursor, Barrett's oesophagus (BO), combined with endoscopic surveillance and treatment of dysplasia might prevent OAC. This review aimed to systematically explore the public's acceptance and uptake of novel screening strategies for OAC. We systematically searched three electronic databases (Ovid Medline/PubMed, Ovid EMBASE and PsycINFO) from date of inception to July 2, 2021 and hand-searched references to identify original studies published in English on acceptability and uptake of OAC screening. Two reviewers independently reviewed and appraised retrieved records and two reviewers extracted data (verified by one other reviewer). Of the 3674 unique records, 19 studies with 15 249 participants were included in the review. Thematic analysis of findings showed that acceptability of OAC screening is related to disease awareness, fear, belief in benefit, practicalities and physical discomfort. The findings were mapped on the Integrated Screening Action Model. Minimally invasive screening tests are generally well-tolerated: patient-reported outcomes were reported for sedated upper endoscopy (tolerability ++), transnasal endoscopy (tolerability +), tethered capsule endomicroscopy (tolerability +/-), and the Cytosponge-TFF3 test (acceptability ++). In discrete choice experiments, individuals mainly valued screening test accuracy. OAC screening has been performed in trials using conventional upper endoscopy (n = 231 individuals), transnasal endoscopy (n = 966), capsule endoscopy (n = 657) and the Cytosponge-TFF3 test (n = 9679), with uptake ranging from 14·5% to 48·1%. Intended participation in OAC screening in questionnaire-based studies ranged from 62·8% to 71·4%. We conclude that the general public seems to have interest in OAC screening. The findings will provide input for the design of a screening strategy that incorporates the public's values and preferences to improve informed participation. Identification of a screening strategy effective in reducing OAC mortality and morbidity remains a crucial prerequisite. Funding: This study was funded by the Netherlands Organization for Health Research and Development (ZonMw) under grant 555,004,206.